Implementing railway vehicle dynamics simulation in general-purpose multibody simulation software packages. (May 2019) - Tang, Zhao; Yuan, Xiaolin; Xie, Xin; Jiang, Jie; Zhang, Jianjun
Highlights: General-purpose multibody simulation (GPMBS) software packages cannot be directly employed to simulate railway vehicle dynamics but have a lot of inherent advantages compared with specialized railway vehicle dynamics simulation software. This paper proposes a framework to make it possible to use GPMBS software packages to simulate railway vehicle dynamics. A multi-language supported loose coupling method is presented for integrating the self-developed force element programs into GPMBS software packages. A strategy combing the top-down approach and the sub-mechanism feature is recommended to construct the railway vehicle dynamics design and simulation model. Abstract: In terms of simulation efficiency, modelling and visualization, general-purpose multibody simulation (GPMBS) software packages have a lot of inherent advantages compared with specialized railway vehicle dynamics simulation software packages. However, their application is limited due to the absence of specialized force elements and contact models, and thus cannot be directly employed for railway vehicle dynamics simulation. To deal with this issue, this paper proposes a novel framework to use GPMBS software packages to simulate the dynamic behavior of the railway vehicle. This framework contains a loose coupling method, a sub-mechanism feature and a top-down modelling method and allows users to take full advantage of the advanced functionalities of the GPMBS software packages to improve the efficiency of railway vehicle dynamics simulation. The feasibility of this framework is verified by integrating extensions for two representative GPMBS software packages. In addition, the two comparisons between the self-developed extensions (for LMS Virtual.Lab Motion and Unity3D) and the widely used specialized railway vehicle dynamics simulation software (Simpack and Universal Mechanism), further confirm the validity of the framework.